Sarah and the thesaurus - Laughlin, Catherine; Bland, Nicholas (Macmillan Education Australia South Yarra [Vic.], 1999)
Sarah and the Thesaurus by Eileen Hollander is a charming children's book that tells the story of a young girl named Sarah who discovers the wonders of a thesaurus. Fascinated by words, Sarah learns how a thesaurus can help her find new and exciting ways to express herself. The book encourages a love of language and creativity as Sarah embarks on a journey of exploring synonyms and enriching her vocabulary. Through her adventures with words, Sarah gains confidence in writing and speaking, making this a delightful story about learning and self-expression for young readers.